A liquid-free poly(butylene oxide) electrolyte for near-room-temperature and 4-V class all-solid-state lithium batteries. (December 2021) - Luo, Jing; Sun, Qian; Liang, Jianneng; Yang, Xiaofei; Liang, Jianwen; Lin, Xiaoting; Zhao, Feipeng; Liu, Yulong; Huang, Huan; Zhang, Li; Zhao, Shangqian; Lu, Shigang; et al.
Abstract: Solid polymer electrolyte (SPE) is a promising class of solid electrolytes for building All-solid-state lithium batteries (ASSLBs) due to their flexibility and compatibility with electrodes. However, the requirement of an elevated operating temperature (> 60 °C) and the high-voltage instability remain major drawbacks for the most commonly used poly(ethylene oxide) (PEO) SPEs. Alternatively, poly(butylene oxide) (PBO) is another member of the polyether family that shows significantly enhanced ionic conductivity at room temperature, but its application in ASSLBs is rarely investigated, probably due to challenges of engineering methodology and interfacial stability. Herein, we develop a solvent-free fabrication route for building PBO SPE membrane for application in ASSLBs with feasible performance near room temperature. We demonstrate a facile activation methodology to stabilize the electrode/electrolyte interface for the PBO based ASSLBs. As a result, the ASSLB with a LiFePO4 cathode delivers a stable specific capacity of 140 mA h g −1 at 0.1 C with almost 100% retention after 100 cycles near room temperature. Moreover, despite the poor high-voltage stability of PEO, we found that the PBO SPE presents good compatibility with 4-V class cathodes without any additional coating, achieving a capacity retention of 94.6% over 100 cycles with a conventional LiCoO2 cathode at 60 °C. This work shall inspire new possibilities of dry SPEs development for ASSLBs. Graphical Abstract: We demonstrate a poly(butylene oxide) based dry solid polymer electrolyte (SPE) that is feasible near room temperature and compatible with 4-V class cathodes, simultaneously solving two key challenges of SPE based all-solid-state batteries. ga1 Highlights: A solvent-free route for fabricating solid polymer electrolyte (SPE) membrane based on poly(butylene oxide) (PBO). All-solid-state batteries using PBO SPE show feasible performance near room temperature without plasticizer additives. An electrochemical activation process can facilitate in-situ formation of a favorable cathode electrolyte interphase (CEI). The PBO SPE presents good compatibility with 4-V class cathodes without any additional coating.